Numerical simulation of exterior condensations on façades: The undercooling phenomenon - J. M. P. Q. Delgado (2010)
This manuscript presents a brief state-of-the-art on the development and application of hygrothermal analysis methods tosimulate the coupled transport processes of heat and moisture for one or multidimensional cases.This work intends to apply existing numerical models of exterior boundary conditions on the simulation of exterior condensationon façades (undercooling phenomenon) finished with external thermal insulation composite systems (ETICS). The resultsof three hygrothermal models were compared, regarding the temperature on the exterior surface of a west façade. The climaticconditions from the city of Porto, Portugal were used. We analyzed in detail how the simulation of the undercooling phenomenonis influenced by the numerical treatment of the radiative balance on the exterior surface.The numerical results show that these programs are useful tools in assessing the exterior condensation on façades and theimportance of radiative balance on the exterior surface temperature. However, some differences were observed in the calculatedvalues due to different parameters included in the radiative balance of the models.